1971
DOI: 10.1128/jb.108.3.1200-1204.1971
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethidium Bromide on Growth and on Loss of the Penicillinase Plasmid of Staphylococcus aureus

Abstract: Ethidium bromide (EB) was more efficient than ethyl violet or rifampin as a curing agent for the penicillinase plasmids of Staphylococcus aureus strains. The effects of EB on growth and on the loss of the penicillinase plasmid of PS 81 were studied in detail. The growth rates of PS 81 and an EB-cured derivative were identical in broth, but the cured derivative had a shorter lag in the presence of added 6 x 10-6 M EB. The shortened lag was due to prior exposure to EB as the cured derivative and an EB-treated bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…Sporulation of strain EB8 was blocked when grown in the presence of EB (10 jig/ml) on either AK agar or in x 2 Shaeffer sporulation medium. After 16 h of growth at 37 C with vigorous shaking in x 2 Shaeffer medium containing 10 Ag of EB/ml, microscope examination revealed no spores or intermediate stages. However, the cells were highly motile and their morphology appeared normal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sporulation of strain EB8 was blocked when grown in the presence of EB (10 jig/ml) on either AK agar or in x 2 Shaeffer sporulation medium. After 16 h of growth at 37 C with vigorous shaking in x 2 Shaeffer medium containing 10 Ag of EB/ml, microscope examination revealed no spores or intermediate stages. However, the cells were highly motile and their morphology appeared normal.…”
Section: Resultsmentioning
confidence: 99%
“…Ethidium bromide (EB) (2, 7-diamino-9phenylphenanthridium-1-ethyl bromide) has been used for a variety of biological purposes. EB induces petite mutations in yeast (19), it has been used to eliminate penicillinase plasmids and resistance transfer factors from bacterial cells (2,16), it is an inhibitor of nucleic acid biosynthesis (20), and it functions as a mutagen in bacterial cells (13).…”
mentioning
confidence: 99%
“…Curing was usually observed at a high frequency, and the results obtained were more reproducible than with acridine dyes. Rubin and Rosenbaum [19] also successfully cured peni.cillinase plasmids in Staphylococcus aureus strains using ethidium bromide.…”
Section: Intercalating Dyesmentioning
confidence: 99%
“…Various physical and chemical agents can be used to enhance the frequency of plasmid elimination over that of spontaneous loss, but the frequencies of elimination will vary according to the strain and conditions used (16). The increased loss or curing of genetic markers after growth of some strains in curing agents or at elevated temperatures is indicative of plasmid location of the markers, but only if it can be shown that treatment did not select for cells from which plasmid markers were lost spontaneously (17). Possible selective effects can be ruled out (i) by determining the rate and time of appearance of negative variants during treatment of the wild-type culture, and (ii) by showing that growth at the elevated temperature or in the presence of the curing agent does not competitively favor plasmid-negative cells over plasmid-positive cells (9,17).…”
mentioning
confidence: 99%
“…Ethidium bromide (EB) has proven to be a potent agent for eliminating penicillinase plasmids (3,14,17). Rubin and Rosenblum (17) observed that the curing frequencies for staphylococcal penicillinase plasmids were consistently greater with EB than with other curing agents.…”
mentioning
confidence: 99%